An exploration of the school nutrition programme's potential to catalyse community-based environmental learning : a case study of a rural Eastern Cape school - Tshabeni, Veliswa (Rhodes University, Faculty of Education, Department of Education, 2015)
The purpose of this study was to explore the extent to which a School Nutrition Programme can catalyse community-based environmental learning and promote food security in the school and the community. This is an interpretive case study of a junior secondary school in the rural Eastern Cape province of South Africa. The school is located in an area characterised by high levels of poverty and under-nutrition. The school's food garden, a central focus of this study, contributes to the School Nutrition Programme, which falls under the National School Nutrition Programme (NSNP). The aim of the NSNP is to alleviate poverty in public schools. This case study was conducted by means of questionnaires, semi-structured interviews, and document analysis and field observations. The data set was analysed, firstly, to ascertain if the School Nutrition Programme functions as a community of practise (Wenger, 1998). Thereafter, the data set was analysed to identify the knowledge related to food security and environmental sustainability that is learned and shared in the School Nutrition Programme, and also how such learning took place. The study found that the School's Nutrition Programme was indeed operating as a community of practice and that it created a platform for sharing explicit and tacit knowledge and skills related to food security and environmental sustainability. The case study also revealed the contextual and experience-based nature of knowledge related to food cultivation.
Keywords: National School Nutrition Programme (South Africa); School children -- Food -- South Africa -- Eastern Cape; Children -- Nutrition -- South Africa -- Eastern Cape; Environmental education -- South Africa -- Eastern Cape; Social learning -- South Africa -- Eastern Cape; Food security -- South Africa -- Eastern Cape; Rural development -- South Africa -- Eastern Cape; Poverty -- South Africa -- Eastern Cape